Studi Kelayakan Bisnis Pada UMKM French Fries Potacio Bliss di Kota Bandung - Hadiyan Kamil, Adhitya Muhdan; Meylani, Nilam; Nur Zaman, Luqman; Asthian, Youza; Perwito, Perwito (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Potacio Bliss is designed to meet the market's needs for innovative and up-to-date high-quality snacks. French fries have great potential in the modern culinary industry as one of the most popular types of snacks in various circles. This article examines in-depth technical and production aspects, ranging from the selection of raw materials to the packaging stage, designed to ensure that the quality of products is maintained. The production stage starts from premium quality potato selection, standardized processing, to frying with modern technology to produce a perfect texture. This process is supported by innovations in topping and sauce variants that create a unique and attractive taste for consumers. By utilizing technology equipment and efficient production techniques, Potacio Bliss is able to present consistent products while optimizing its production scale. Through strict quality control and the use of environmentally friendly packaging, this business focuses not only on product quality but also on environmental sustainability. This study aims to provide technical guidance for snack business operators and identify strategic steps in increasing competitiveness in the market. In conclusion, innovation in technical aspects and production became a key factor in the success of French fries businesses such as Potacio Bliss in responding to modern market challenges.